The economic security as a national priority: the impact of external and internal factors (Journal of Economic Research & Business Administration, 2016)
Economic security is a complex of economic, geopolitical, legal political, geostrategic conditions. Through dynamic growth, resource of potential, social development and environmental security is to protect the public interest.According to many authors, economic security is characterized as the impact of economic systems on stability under the influence of internal and external factors, and stability , in turn , provides its development. If there is no economic development, reduced level of survivability.
Keywords: economic security; national economy; national security; factors affecting economic security; economic interest; the path of eco nomic security; national strategy for economic security.